Enhancing Skincare Purchase Decisions: A Case Study of Facetology in Semarang City - Anisah Gadiez Salsa Aprilleony; Mahmud Mahmud; Bara Zaretta; Febrianur Ibnu Fitroh Sukono Putra (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to analyze the influence of brand image, word of mouth, and product quality on the purchase decision of Facetology skincare products. The study uses a quantitative method to obtain objective and generalizable results. The sample consisted of 100 respondents, who were individuals who had purchased or used Facetology skincare products. The sampling technique used was purposive sampling, ensuring that the selected respondents met criteria relevant to the research objectives. Data collection was conducted through the distribution of questionnaires to the selected respondents to gather the necessary information. The data analysis technique employed was Smart PLS 4.0, which efficiently and accurately measures the relationships between variables. This study emphasizes the importance of understanding the factors influencing purchase decisions in the skincare industry, particularly for the Facetology brand. The results of the study indicate that word of mouth has a positive and significant effect on the purchase decision of Facetology products. Additionally, brand image was found to have no significant effect on the purchase decision, while product quality had a positive and significant effect on the purchase decision of Facetology products. The implications of this study suggest that the company can leverage word of mouth as an effective marketing strategy and focus more on improving product quality to influence consumer purchase decisions.